2016
DOI: 10.3389/fmicb.2016.01962
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Differential Expression of Cellular Proteins in Response to Avian H9N2 Virus Infection of A549 Cells

Abstract: In this study, differentially expressed proteins in A549 cells (human lung adenocarcinoma epithelial cell line) infected with H9N2 avian influenza virus (AIV) were investigated by two-dimensional electrophoresis (2-DE). Sixteen different spots between the groups (ratio > 2, p < 0.05) were identified with mass spectrometry identification. Proteins located in the downstream of the NF-κB and IFN transcription factor pathways were identified, e.g., ISG15. Actin and keratin were also identified, suggesting that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Third, IAV infection alters the levels, structures, and functions of F-actin and microtubules in host cells. Several studies show an enhancement in total actin [85,86] and tubulin [87] levels upon infection. However, one study showed no difference in cellular actin levels [88], and another showed a reduction in tubulin levels [85] upon IAV infection.…”
Section: Relationships Between Virus Growth and Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, IAV infection alters the levels, structures, and functions of F-actin and microtubules in host cells. Several studies show an enhancement in total actin [85,86] and tubulin [87] levels upon infection. However, one study showed no difference in cellular actin levels [88], and another showed a reduction in tubulin levels [85] upon IAV infection.…”
Section: Relationships Between Virus Growth and Cytoskeletonmentioning
confidence: 99%
“…Several studies show an enhancement in total actin [85,86] and tubulin [87] levels upon infection. However, one study showed no difference in cellular actin levels [88], and another showed a reduction in tubulin levels [85] upon IAV infection. In addition to total actin and tubulin levels, IAV infection can also modulate the levels or activities of proteins involved in the regulation of F-actin and microtubule dynamics.…”
Section: Relationships Between Virus Growth and Cytoskeletonmentioning
confidence: 99%
“…[69][70][71] The increase in CK14 suggests a possible role of the cytoskeleton in IAV infection, as suggested previously. 72 Changes in mRNA expression of cellular markers. To understand whether the changes in marker proteins in 3Dcultured HSAEpCs occurred transcriptionally, we studied the effect of infection on the mRNA expression of Aqp5, CC-10, CK-14, and SP-C genes.…”
Section: Figmentioning
confidence: 99%
“…Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2 (NOX2), critical for expression of reactive oxygen species (ROS), is often activated in endocytic compartments by RNA and DNA viruses, exacerbating virus-mediated pathogenicity [ 104 • ]. In addition to important roles for host proteins [ 105 ], the role of lipids [ 74 •• ] in respiratory virus infections has also drawn increasing attention. Zhao et al reported that age-related increases in prostaglandin D2 (PGD 2 ) expression in mouse lungs correlated with a progressive impairment in DC migration to DLNs, causing diminished T cell responses upon IAV or SARS-CoV infection [ 106 ].…”
Section: Modulation Of Immune Responses Against Respiratory Virus Infmentioning
confidence: 99%